Developmental Changes in Calcium Channel Types Mediating Central Synaptic Transmission - Iwasaki, Shinichi (J Neurosci, 2000)
Multiple types of high-voltage-activated Ca(2+)channels trigger neurotransmitter release at the mammalian central synapse. Among them, the ω-conotoxin GVIA-sensitive N-type channels and the ω-Aga-IVA-sensitive P/Q-type channels mediate fast synaptic transmission. However, at most central synapses, it is not known whether the contributions of different Ca(2+) channel types to synaptic transmission remain stable throughout postnatal development. We have addressed this question by testing type-specific Ca(2+) channel blockers at developing central synapses. Our results indicate that N-type channels contribute to thalamic and cerebellar IPSCs only transiently during early postnatal period and P/Q-type channels predominantly mediate mature synaptic transmission, as we reported previously at the brainstem auditory synapse formed by the calyx of Held. In fact, Ca(2+) currents directly recorded from the auditory calyceal presynaptic terminal were identified as N-, P/Q-, and R-types at postnatal day 7 (P7) to P10 but became predominantly P/Q-type at P13. In contrast to thalamic and cerebellar IPSCs and brainstem auditory EPSCs, N-type Ca(2+) channels persistently contribute to cerebral cortical EPSCs and spinal IPSCs throughout postnatal months. Thus, in adult animals, synaptic transmission is predominantly mediated by P/Q-type channels at a subset of synapses and mediated synergistically by multiple types of Ca(2+)channels at other synapses.